Penyelesaian Sengketa Keputusan Tata Usaha Negara Melalui Upaya Banding Administratif - Abdul Khair; Sunarjo Edy Siswanto; Sarkawi -; Muhammad Saleh (Jatiswara, 2016)
The purpose of this study was to determine and analyze the dispute resolution process KTUN through appeals of administration according to Law Number 51 Year 2009 regarding the Second Amendment to Law Number 05 Year 1986 concerning State Administrative Court and to know and analyze the strengths and weaknesses in the process dispute resolution through an administrative appeal case in Indonesia. This research is a normative empirical research, the method of approach to legislation, analytical approach. The results of the study are as follows: (1) The process of dispute resolution KTUN through the efforts of Appeals Administration according to Law Number 51 Year 2009 regarding the Second Amendment to Law Number 05 Year 1986 regarding Administrative Court Negaraialah dispute resolution TUN administratively conducted by agencies supervisor or other agencies from issuing the decision in question. Administrative appeals procedure is done by filing an administrative appeal letter addressed to the head of an official or other agencies and bodies / administrative official of the State which issued a decision that the authority to examine the disputed KTUN (SEMA 2 of 1991 dated July 9, 1991). Judging from the elucidation of Article 48 of Law Administrative Court, there are two categories of institutions / agencies authorized to deal with the Administrative Appeal, namely: (a) Agencies supervisor of officials who issued KTUN and; (B) any other authorized. While Strengths and Weaknesses in the Settlement of Disputes through the Administrative Appeals Efforts in Indonesia is; (1) Ratings administrative effort carried out fully against an administrative decision both in terms of legality (rechtmatigheid) as well as aspects Opportunitas (doelmatigheid) (2) the Parties are not faced with the decision win or lose (Winor Loose) as well as in the judiciary; (3) approach to dispute resolution is done with deliberation; (4) The trial is simple and quick no such formality in the Administrative Court; (5) There is no need to pay money matters; (6) Completed at internal concerned agencies; (7) An appeal is not bound to wear procedural administrative proceedings such as in the Administrative Court; (8) Do not need a lawyer; (9) The decision according to desire of the applicant; (10) Direct executable (strong eksekutorial). Weakness Settlement through the Administrative Appeals Efforts are; (1) At the level of objectivity of the assessment for the Agency / State Officials system that issued the Decree is sometimes associated interests, directly or indirectly, thereby reducing the maximum assessment that should be pursued; (2) There are no definite rules specifically time expired ratings or siding; (3) There is a chance of ignoring the report or appeal an administrative person.